1990
DOI: 10.1007/bf02401421
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of mitochondrial DNA (mtDNA) in cattle and buffaloes

Abstract: Mitochondrial DNA (mtDNA) from two breeds of cattle, viz., [Hariana (Bos indicus), Holstein (Bos taurus)] and Indian water buffalo (Bubalis bubalus), was analyzed using 13 restriction endonucleases which recognized an average of about 40 six-base sites. Polymorphism among cattle was detected with six of these enzymes. The two Holstein differed at six sites, whereas the Hariana breed (Bos indicus) did not show any site polymorphism. Surprisingly, the Hariana type differed by only one site from one of the Holste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 10 publications
(5 reference statements)
1
23
0
Order By: Relevance
“…Therefore, finding genetic markers have been focused on mtDNA, improving availabilities of abundant mutation sites to perform population studies and identifying individuals as well as breeds. Before applying SNP in genetic studies, RFLP (restriction fragment length polymorphism) analysis using restriction enzymes [10][11][12][13] was firstly reported as genetic variants by Laipis et al [14]. After development of sequencing technology, SNP are the most major markers to differentiate individual characterizations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, finding genetic markers have been focused on mtDNA, improving availabilities of abundant mutation sites to perform population studies and identifying individuals as well as breeds. Before applying SNP in genetic studies, RFLP (restriction fragment length polymorphism) analysis using restriction enzymes [10][11][12][13] was firstly reported as genetic variants by Laipis et al [14]. After development of sequencing technology, SNP are the most major markers to differentiate individual characterizations.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies examining differences in bovine mtDNA, with the exception of studies such as those by Loftus et al (1994a), Mannen et al (1998Mannen et al ( , 2000 and Cymbron et al (1999), have traditionally used polymorphism in restriction enzyme cleavage pattern (e.g., Watanabe et al 1985Watanabe et al , 1989Bhat et al 1990;Kikkawa et al 1995;Parfitt and Huismans 1998). These studies were successful in revealing breed differences but, as RFLP analysis cannot identify variation that is present at sites other than those specific for restriction enzyme cleavage, a fair amount of variation was probably missed by these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Holstein cattle were only recognized as a separate breed from the Friesian nearly 80 yr ago; therefore the variability between the two breeds was expected to be narrow. Bhat et al (1990) and Watanabe et al (1985) characterized variations in mtDNA restriction enzyme cleavage patterns within and between various European, North American, Indian and Asian cattle breeds. Similarly, Loftus et al (1994a, b) have demonstrated, using both restriction fragment length polymorphism (RFLP) analysis of mtDNA and mtDNA D-loop sequence variation, that while numerous differences among and within breeds can be identified, sequence variation between European and African (Bos taurus) cattle breeds is not significant enough to point to more than one major mitochondrial lineage.…”
Section: Discussionmentioning
confidence: 99%
“…It can also act as a weak transcriptional regulator in the absence of Gal3p [11]. When grown on a medium, where galactose is present as a sole carbon source, null mutants for GAL1 are unable to metabolize galactose and grow [12, 13]. This protein shares a high similarity of 90% in amino acids with Gal3p [12].…”
Section: Introductionmentioning
confidence: 99%